063 Quality improvement project on reducing laboratory sample rejection due to pre-analytical errors – improving patient experience, quality and efficiency. (December 2018) - Musabaike, W; Wu, Y; Morris, C; Heales, S
Abstract : Introduction: It is estimated that 70% of diagnostic clinical decisions are based upon information derived from laboratory test results. While laboratories have strived to minimise errors in analytical processes, evidence suggests that over 60% of laboratory errors happen during the pre-analytical stages, e.g., during sample collection and transport. At the Great Ormond Street Hospital for Children, an audit revealed over 4500 (1.0%) patient samples were rejected in 2017 due to pre-analytical errors. There is evidence that some laboratories are under-reporting incidents which implies the scale of the problem is significantly higher. Sample re-collection and re-testing not only cause delayed diagnosis and treatment, but also result in a wastage of staff time and hospital resources. Most importantly of all, patients are subject to unnecessary collection procedures (e.g., needle poke) that are often associated with negative feelings. Methods: A quality improvement project that aims at developing the organisations capabilities to reduce the number of pre-analytical patient sample rejections started in April 2018. Several audits on rejected and delayed laboratory samples have been performed, e.g., delayed blood cultures, leaking nasopharyngeal aspirates (NPA) during transit and reasons for rejection of blood coagulation samples. Results: The findings of these audits were communicated to different clinical and management teams to raise concerns, which resulted in collective efforts in putting remedial actions into effect. The improvement that followed was underpinned by the use of tools such as driver diagram and stakeholder map. Discussion: A Trust-wide steering group has been formed to monitor and ensure sustainability of this improvement project, the latest findings from the project will be presented at the conference.